Leptohadronic Multimessenger Modeling of Two High-redshift (z > 1) Neutrino Emission Blazar Candidates - Xiong Jiang; Neng-Hui Liao; Rui Xue; Yi-Zhong Fan; Da-Ming Wei (The Astrophysical Journal)
The blazars are one of the leading candidate sources of high-energy neutrinos. Recently, two blazars have been found to be temporally and spatially correlated with some IceCube high-energy neutrino events. The two blazars, GB6 J2113+1121 and NVSS J171822+423948, are flat spectrum radio quasars (FSRQs) with redshifts greater than unity. In particular, NVSS J171822+423948 has a redshift of 2.7, which provides an important probe for studying the radiation processes of jets from active galactic nuclei in the early Universe. To better understand the physical origin of the IceCube neutrinos, we adopt the one-zone leptohadronic model to fit the multimessenger emission of GB6 J2113+1121 and NVSS J171822+423948 during their γ -ray flaring periods and then calculate the high-energy neutrino detection probability. The chance of detecting a single muon neutrino from these two sources is found to be ∼2% and 0.8%, respectively. Although such detection rates are not high mainly because of their high redshifts, our investigation strongly suggests that these sources are efficient PeV neutrino emitters. Our results also indicate that electromagnetic cascades produced by hadronic processes contribute significantly to X-ray and γ -ray emissions. However, high-energy γ -rays can be severely absorbed by the soft photon field from the broad-line region, which weakens the correlation between γ -rays and neutrinos, while suggesting a stronger connection between X-rays and neutrinos. We predict that IceCube will continue to detect neutrinos from FSRQs with redshifts greater than 1 in the future.